Encapsulated aromatic citronella extract (Cymbopogon nardus) and its responses to protein content, solubility, and water holding capacity of catfish bone powder - Khairi, Amalya Nurul; Nuraisyah, Fatma; Sirajuddin, Muhammad Mar'ie; Mufrodi, Zahrul; Khasanah, Aulia Ushwatun (Journal of Halal Science and Research, 2024)
Aromatic citronella contains highly bioactive components that are easily degraded during processing and storage. Their stability decreases due to heat, light, and oxygen exposure. Encapsulation is one method to maintain the stability of bioactive components. This study aims to determine the content of protein, solubility, and water holding capacity (WHC) of aromatic citronella extracted and encapsulated by various maltodextrin concentrations and foam mat drying temperatures of catfish bone powder. The experimental design in this study used a completely randomized design (CRD) with two factors. Temperature variations in this study were 70°C and 80°C, and maltodextrin concentrations were 10% and 15%. Statistical analysis was performed with two-way ANOVA and continued with the DMRT (Duncan's Multiple Range Test) test at the significance level α = 5%. Total protein of encapsulated aromatic citronella extract on catfish bone powder ranged from 17.24-27.34%, solubility ranged from 34.53-55.64%, and WHC ranged from 4.49 – 43.03%. Maltodextrin concentration significantly affected protein content and WHC. Drying temperatures significantly affected the solubility of catfish bone powder with the addition of encapsulated aromatic citronella.